The day Dancer flew : inspired by a true story - Stone, Tiffany, 1967-; Lane, Brittany ([Victoria, British Columbia] : Orca Book Publishers, 2024)
"In this beautiful picture book based on a true story, flooding forces a child and their family to flee their farm without their beloved horse, Dancer. But the child won't give up on Dancer and finds helpers in the community who get Dancer airlifted to safety."--
Issued also in electronic formats.
Keywords: Horses -- Juvenile fiction; Floods -- Juvenile fiction; Rescues -- Juvenile fiction; Helicopters in search and rescue operations -- Juvenile fiction; Horses -- Fiction; Floods -- Fiction; Rescues -- Fiction; Helicopters -- Fiction; JUVENILE FICTION / Animals / Horses; JUVENILE FICTION / Nature & the Natural World / General; Northwest, Pacific -- Juvenile fiction; Northwest, Pacific -- Fiction; picture books; Fiction; Picture books; Picture books; Fiction; Livres d'images.; Romans